Genome-Wide Identification and Expression of Xenopus F-Box Family of Proteins - Saritas-Yildirim, Banu (PLoS One, 2015)
Protein degradation via the multistep ubiquitin/26S proteasome pathway is a rapid way to alter the protein profile and drive cell processes and developmental changes. Many key regulators of embryonic development are targeted for degradation by E3 ubiquitin ligases. The most studied family of E3 ubiquitin ligases is the SCF ubiquitin ligases, which use F-box adaptor proteins to recognize and recruit target proteins. Here, we used a bioinformatics screen and phylogenetic analysis to identify and annotate the family of F-box proteins in the Xenopus tropicalis genome. To shed light on the function of the F-box proteins, we analyzed expression of F-box genes during early stages of Xenopus development. Many F-box genes are broadly expressed with expression domains localized to diverse tissues including brain, spinal cord, eye, neural crest derivatives, somites, kidneys, and heart. All together, our genome-wide identification and expression profiling of the Xenopus F-box family of proteins provide a foundation for future research aimed to identify the precise role of F-box dependent E3 ubiquitin ligases and their targets in the regulatory circuits of development.